Inventario de la flora vascular de Jalisco, México - Ana Karem Gudiño-Cano; José Arturo De-Nova; Enriquez Ortíz; Ofelia Vargas-Ponce; Pablo Carrillo-Reyes; Guadalupe Munguía-Lino; José Luis Villaseñor; Eduardo Ruiz-Sanchez (Botan‪ical Sciences)
Background: Floristic inventories record the species observed in a particular region and serve as fundamental contributions to understanding biotic resources. Jalisco stands out as one of the Mexican states with significant floristic diversity. However, ongoing additions, documented through exploratory efforts, and periodic taxonomic revisions highlight the importance of maintaining an up-to-date inventory of vascular plants.